2021
DOI: 10.1371/journal.pbio.3001418
|View full text |Cite
|
Sign up to set email alerts
|

Noise-trained deep neural networks effectively predict human vision and its neural responses to challenging images

Abstract: Deep neural networks (DNNs) for object classification have been argued to provide the most promising model of the visual system, accompanied by claims that they have attained or even surpassed human-level performance. Here, we evaluated whether DNNs provide a viable model of human vision when tested with challenging noisy images of objects, sometimes presented at the very limits of visibility. We show that popular state-of-the-art DNNs perform in a qualitatively different manner than humans—they are unusually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…This research extends previous work showing that DNNs are severely affected by various image corruptions and that the patterns of errors they make on such images do not mirror the mistakes that humans make [5]. The SSNR threshold for the noise-trained DNN reported by Jang and colleagues was slightly lower than that of the human viewers [3]. This is in line with previous work, which found that data augmentation can lead to superhuman performance on the specific image corruptions seen during training [6].…”
supporting
confidence: 80%
See 3 more Smart Citations
“…This research extends previous work showing that DNNs are severely affected by various image corruptions and that the patterns of errors they make on such images do not mirror the mistakes that humans make [5]. The SSNR threshold for the noise-trained DNN reported by Jang and colleagues was slightly lower than that of the human viewers [3]. This is in line with previous work, which found that data augmentation can lead to superhuman performance on the specific image corruptions seen during training [6].…”
supporting
confidence: 80%
“…Rusak and colleagues [7] also demonstrated that careful noise training can help DNNs generalize to unseen image corruptions as well. The neuroimaging results presented by Jang and colleagues [3] provides novel evidence that noise training brings the network's internal information processing, not just its output, into greater alignment with that of the human visual system.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Viewpoint invariance is a computationally challenging process because viewpoint changes, particularly the rotation of an object in depth, can radically change the shape of the object on the retina (Marr & Nishihara, 1978). Indeed, despite the success of artificial neural networks (ANNs) in several domains of object recognition (Jang, McCormack, & Tong, 2021;Kriegeskorte, 2015), identifying objects from unfamiliar orientations remains difficult even for state-of-the-art models (Barbu et al, 2019). By contrast, human adults readily identify objects from novel orientations, even when the objects are unfamiliar (Biederman & Bar, 1999;Humphrey & Jolicoeur, 1993;Tarr & Bülthoff, 1995).…”
Section: Viewpoint Invariancementioning
confidence: 99%